Analisis Komunikasi Narasi Flexing Sebagai Strategi Pemasaran Digital dan Implikasinya Terhadap Generasi Z - Nugroho Rizki Ramadhan ramadhan; Dr. Elisabeth Nugrahaeni Prananingrum (Journal of Media and Communication | E-ISSN : 3063-9581, 2026)
This study analyzes the phenomenon of flexing on social media, which has evolved into a kind of strategic communication tactic, using a luxurious lifestyle for commercial or personal purposes. The main goal of this research is to see how the flexing narrative is shaped through digital platforms and to examine the communication impact on audience behavior, especially Generation Z. Using a qualitative approach and case study method, data was collected from various secondary sources, such as online news reports, journal articles, and research reports related to public figures like Indra Kenz and Doni Salmanan. Content analysis and visual semiotics were used to break down the elements of the narrative being built. The results show that the flexing narrative is like a deliberately staged performance, which can be understood through dramaturgy theory. This narrative creates an eye-catching and impressive “front stage,” but hides a “back stage” that is often linked to manipulative or even illegal practices. The study concludes that flexing narratives are not just about showing off wealth, but also a manipulative communication strategy, putting audiences, especially young people, in a vulnerable position toward harmful consumerist mentalities and scam schemes. These findings highlight the importance of boosting digital literacy for young people or Gen Z so they can distinguish between genuine and manipulative content. The contribution of this research lies in adding to applied communication studies by providing a critical understanding of manipulative digital communication strategies and their impact on young people.